Strengthening the Reputation of Islamic Boarding Schools: The Role of Leadership, Educational Innovation, and Local Wisdom - Thohir, Putri Fahmadia Dinda Maulida; Baharun, Hasan (Universitas Nurul Jadid, 2024)
This study aims to analyze the influence of leadership, educational innovation, and local wisdom on strengthening the reputation of Islamic boarding schools. This study tests four hypotheses related to the impact of these variables on the reputation of Islamic boarding schools. The first hypothesis tests the positive influence of leadership (X1) on strengthening the reputation of Islamic boarding schools (Y), the second hypothesis tests the positive influence of educational innovation (X2) on strengthening the reputation of Islamic boarding schools (Y), the third hypothesis tests the positive influence of local wisdom (X3) on strengthening the reputation of Islamic boarding schools (Y), and the fourth hypothesis tests the positive influence of leadership, educational innovation, and local wisdom simultaneously on strengthening the reputation of Islamic boarding schools. Data were collected through questionnaires with a sample of 260 respondents and analyzed using simple regression tests and multiple regression with the help of the SPSS Statistics program. The results of the study showed that leadership (X1) had a significant positive effect with a t-value of 13.083 and a p-value of 0.000, educational innovation (X2) had a significant positive effect with a t-value of 7.927 and a p-value of 0.000, and local wisdom (X3) had a significant positive effect with a t-value of 8.927 and a p-value of 0.000. In addition, the results of the multiple regression test showed that the three variables had a significant positive effect simultaneously on strengthening the reputation of Islamic boarding schools, with t-values for leadership (5.916), educational innovation (2.285), and local wisdom (2.825), and p-values of 0.000, 0.035, and 0.055, respectively. Overall, these three factors implies greatly to strengthening the reputation of Islamic boarding schools, which is important for the continuity and development of Islamic boarding schools in the future.